Two steps for scoring a point: Creating and converting opportunities in invasion team sports - Lamas, L.; Senatore, J. V.; Fellingham, G. (PLOS ONE, 2020)
In invasion team sports, scoring efficiency depends on the ability to create scoring opportunities and to convert them into goals or points. Scoring performance varies across sports and comparisons among them are little. In this paper we compare creation and conversion of scoring opportunities in different team sports and genders. Box-score data from six sports [basketball, handball, water polo, field hockey, football, ice hockey] (328 teams, 5723 games, both genders) were standardized by "per ball possession". We applied Bayesian methods to compute the posterior distributions of shots per possession (SHTpPOS), points per shot (PTSpSHT) and points per possession (PTSpPOS). We evaluated differences for these three variables among sports, between genders and the correlation between every pair of them. Inter-sports evaluation evidenced basketball, handball, ice hockey and water polo are sports with a high probability of creating shots (SHTpPOS—p(robability) > 0.65). Complementary, ice hockey, field hockey and football are sports with a low probability of converting shots (PTSpSHT—0.05 < p < 0.26). Despite the distinct results among sports for creating and converting opportunities, all sports in both genders, converged to a scoring efficiency (PTSpPOS) below 0.5. In the genders` comparison, men are more efficient in creating opportunities than women, except in water polo. For scoring efficiency, differences between men and women are fewer. Results prevent generalization about differences in scoring efficiency between genders. Finally, creation and conversion have low correlation in sports with high shot creation probabilities (basketball and ice hockey). In these sports, scoring is not limited by the number of shots taken but rather by their accuracy. For sports with low shot creation probabilities (soccer and men field hockey), creation and conversion presented higher correlation. Evidences contribute to increase coaches` understanding about scoring tactics` challenges in team sports and design practices accordingly.